Effects of graphite and Mn ore media on electro-active bacteria enrichment and fate of antibiotic and corresponding resistance gene in up flow microbial fuel cell constructed wetland - Li, Hua; Xu, Han; Yang, Yu-Li; Yang, Xiao-Li; Wu, You; Zhang, Shuai; Song, Hai-Liang (Water research (Oxford), 2019)
This study assessed the influence of substrate type on pollutants removal, antibiotic resistance gene (ARG) fate and bacterial community evolution in up-flow microbial fuel cell constructed wetlands (UCW-MFC) with graphite and Mn ore electrode substrates. Better COD removal and higher bacterial community diversity and electricity generation performance were achieved in Mn ore constructed UCW-MFC (Mn). However, the lower concentration of sulfadiazine (SDZ) and the total abundances of ARGs were obtained in the effluent in the graphite constructed UCW-MFC (s), which may be related to higher graphite adsorption and filter capacity. Notably, both reactors can remove more than 97.8% of ciprofloxacin. In addition, significant negative correlations were observed between SDZ, COD concentration, ARG abundances and bacterial a-diversity indices. The LEfse analysis revealed significantly different bacterial communities due to the substrate differences in the two reactors, and Geobacter, a typical model electro-active bacteria (EAB), was greatly enriched on the anode of UCW-MFC (Mn). In contrast, the relative abundance of methanogens (Methanosaeta) was inhibited. PICRUSt analysis results further demonstrated that the abundance of extracellular electron transfer related functional genes was increased, but the methanogen function genes and multiple antibiotic resistance genes in UCW-MFC (Mn) anode were reduced. Redundancy analyses indicated that substrate type, antibiotic accumulation and bacterial community were the main factors affecting ARGs. Moreover, the potential ARG hosts and the co-occurrence of ARGs and intI1 were revealed by network analysis. [Display omitted] •The electro-active bacteria Geobacter was greatly enriched on Mn ore anode.•Methanogen functional genes predicted by PICRUSt reduced on Mn ore anode.•Higher COD removal and electricity generation performance was obtained in UCW-MFC (Mn).•The migration of ARGs and their hosts from water phase to substrate reduced the ARGs.